Financial Analysis of the Private Organic Farm: Sanga Agro Farm - Acharya, Gyanu (Curriculum Development Journal, 2021)
The study was regulated to find out the financial profitability of private organic farm of Sanga, Kavre. The study is based on both primary and secondary sources of data. The collected data using interview were analyzed by presenting them on table and interpreted through Benefit Cost Ratio (BCR) in 10 percent discount rate. For this, all figures were converted into Net Present Value (NPV) of Nepalese rupees. The findings of the study showed that the BCR was greater than one such as 1.47 ratios (BCR>1). The BCR value showed that the farm has contributed to increase more profit of owner by selling their farm’s products. The project of organic items: beans and garden cress was able to produce fresh items, provide space for employment. These organic products supported human health, soil health, and maintained conducive environment.